Desarrollo de un Dashboard para el Análisis de Formalización de Tierras de una Entidad Catastral (2024)
Access to land ownership in Colombia, recognized as a fundamental right by the Constitution, has faced significant challenges due to corruption and management deficiencies in the responsible institutions. Among these institutions are cadastral entities such as the Special Administrative Unit of Cadastre, the Cadastre Management, the Agustín Codazzi Geographic Institute, and the National Land Agency, the latter emerged following the transformation of previous institutions such as the Colombian Institute for Agrarian Reform and the Colombian Institute of Rural Development (Incoder).